2019
DOI: 10.1007/s40071-019-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary Aloe vera polysaccharides supplementation on growth performance, feed utilization, hemato-biochemical parameters, and survival at low pH in African catfish (Clarias gariepinus) fingerlings

Abstract: This study evaluated the effects of dietary Aloe vera polysaccharides on growth performance, feed utilization, hemato-biochemical parameters, and resistance against low water pH in African catfish (Clarias gariepinus) fingerlings. Fish were divided into five triplicate groups before being fed feeds supplemented with 0% (control), 0.5%, 1.0%, 2.0%, and 4.0% A. vera/kg diet for 8 weeks. Fish fed 1.0% A. vera/kg diet had significantly increased (P \ 0.05) growth parameters (i.e., final weight, weight gain, absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 57 publications
3
18
0
4
Order By: Relevance
“…Moreover, glycosides (saponins) present in doum palm are known to form complexes with cholesterol and bile in the intestine, thereby indirectly reducing the cholesterol level in the blood, which may also rationalize this effect of DPFP [24]. Likewise, dietary clove basil leaf extract [62] and Aloe vera polysaccharides [76] have also reported such lipid-lowering activity in African catfish.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glycosides (saponins) present in doum palm are known to form complexes with cholesterol and bile in the intestine, thereby indirectly reducing the cholesterol level in the blood, which may also rationalize this effect of DPFP [24]. Likewise, dietary clove basil leaf extract [62] and Aloe vera polysaccharides [76] have also reported such lipid-lowering activity in African catfish.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome these stressors and improve fish health and welfare, several attempts have been done. For example, improve husbandry system used for fish rearing, use optimum nutrient level, improve water quality and the using of immunostimulants and growth promoters (Gabriel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding aminotransferases (aspartate aminotransferase, AST; and alanine aminotransferase, ALT), these enzymes are used for diagnosing certain hepatic alterations that lead to destruction and necrosis of tissues (Gabriel et al, 2019; Zadmajid & Mohammadi, 2017). In the present study, no additional effect was observed from the treatments with EOs in tambaqui infected with A .…”
Section: Discussionmentioning
confidence: 99%
“…However, reductions in the values for these aminotransferases (AST and ALT) in Clarias gariepinus that was fed a diet supplemented with Aloe vera, in relation to the control, were reported by Gabriel et al (2019). This same author reported that inclusion of Aloe vera in the diet of O. niloticus conferred protection against liver damage caused by S. iniae (Gabriel et al, 2015).…”
Section: Stagementioning
confidence: 99%